Geographical variability of the venoms of four populations of Bothrops asper from Panama: Toxicological analysis and neutralization by a polyvalent antivenom. (15th June 2017) - Vélez, Sara María; Salazar, Marcos; Acosta de Patiño, Hildaura; Gómez, Leandra; Rodriguez, Abdiel; Correa, David; Saldaña, Julio; Navarro, Deyvi; Lomonte, Bruno; Otero-Patiño, Rafael; Gutiérrez, José María
Abstract: Bothrops asper is the medically most important venomous snake in Central America. In Panama, the country having the highest incidence of snakebites in Latin America, B. asper is widely distributed throughout the country and is responsible for the vast majority of snakebites. This study was performed to analyze whether there are variations in the toxicological profile and in some biochemical parameters between the venoms of B. asper from four different regions in Panama. The venoms showed a similar profile of lethal, hemorrhagic, in vitro coagulant, defibrinogenating, edema-forming, myotoxic and indirect hemolytic activities, with subtle quantitative variations between samples of some regions. The venoms also had similar SDS-PAGE patterns and reverse phase HPLC profiles. A polyvalent antivenom manufactured in Costa Rica, and regularly used in Panama, was effective in the neutralization of lethal activity of the venoms of the four populations, with Mean Effective Doses (ED50 ) ranging from 5.98 to 9.72 mg venom/mL antivenom. In agreement, a widespread pattern of cross-reactivity between this antivenom and the four venoms was observed by immunoblotting. Overall, results highlight the lack of marked differences between the venoms of the various populations of B. asper in Panama, and that the antivenom from Costa Rica is effective in neutralizing lethality. Graphical abstract: Highlights: The variability of venoms of Bothrops asper from four regions in Panama was studied. Venoms induced lethality, hemorrhage, coagulation, defibrinogenation, myotoxicity and indirect hemolysis. No significant differences were detected in the toxicity of these venoms, with the exception of myotoxicity. A polyvalent antivenom produced in Costa Rica is effective in neutralizing lethality of these venoms.